Broad-Complex acts downstream of Met in juvenile hormone signaling to coordinate primitive holometabolan metamorphosis - Konopova, Barbora; Jindra, Marek (Development (Cambridge, England), 2008)
Metamorphosis of holometabolous insects, an elaborate change of form between larval, pupal and adult stages, offers an ideal system to study the regulation of morphogenetic processes by hormonal signals. Metamorphosis involves growth and differentiation, tissue remodeling and death, all of which are orchestrated by the morphogenesis-promoting ecdysteroids and the antagonistically acting juvenile hormone (JH), whose presence precludes the metamorphic changes. How target tissues interpret this combinatorial effect of the two hormonal cues is poorly understood, mainly because JH does not prevent larval-pupal transformation in the derived Drosophila model, and because the JH receptor is unknown. We have recently used the red flour beetle Tribolium castaneum to show that JH controls entry to metamorphosis via its putative receptor Methoprene-tolerant (Met). Here, we demonstrate that Met mediates JH effects on the expression of the ecdysteroid-response gene Broad-Complex (BR-C). Using RNAi and a classical mutant, we show that Tribolium BR-C is necessary for differentiation of pupal characters. Furthermore, heterochronic combinations of retarded and accelerated phenotypes caused by impaired BR-C function suggest that besides specifying the pupal fate, BR-C operates as a temporal coordinator of hormonally regulated morphogenetic events across epidermal tissues. Similar results were also obtained when using the lacewing Chrysopa perla (Neuroptera), a member of another holometabolous group with a primitive type of metamorphosis. The tissue coordination role of BR-C may therefore be a part of the Holometabola groundplan.
Keywords: brouci; Protein Isoforms; RNA interference; RNA, Messenger; Juvenile Hormones; konzervovaná sekvence; vývojová regulace genové exprese; Conserved Sequence; Gene Expression Regulation, Developmental; Pupa; signální transdukce; hmyzí proteiny; molekulární sekvence - údaje; Amino Acid Sequence; protein - isoformy; receptory buněčného povrchu; Models, Biological; Signal Transduction; kukla; Metamorphosis, Biological; larva; Animals; biologické modely; ženské pohlaví; zvířata; Coleoptera; Receptors, Cell Surface; sekvence aminokyselin; Insect Proteins; Tribolium; Molecular Sequence Data; Larva; Female; juvenilní hormony; messenger RNA; RNA Interference; biologická proměna